Analysing the hidden curriculum: use of a cultural web - Mossop, Liz; Dennick, Reg; Hammond, Richard; Robbé, Iain (Wiley, 2013)
CONTEXT Major influences on learning about medical professionalism come from the hidden curriculum. These influences can contribute positively or negatively towards the professional enculturation of clinical students. The fact that there is no validated method for identifying the components of the hidden curriculum poses problems for educators considering professionalism. The aim of this study was to analyse whether a cultural web, adapted from a business context, might assist in the identification of elements of the hidden curriculum at a UK veterinary school.